Drug Targets in Kinetoplastid Parasites - Majumder, Hemanta K.; Majumder, Hemanta K. (Advances in Experimental Medicine and Biology, 2008)
If viewed globally, the parasitic diseases pose an increasing threat to human health and welfare. The diseases caused by kinetoplastid protozoan parasites like Leishmania and Trypanosoma continue as a cause of suffering for many millions of people in both tropical and subtropical regions of the world. Leishmania species are found throughout Latin America, Africa and Asia. Trypanosoma cruzi that cause Chagas’ disease is endemic in Latin America, while members of Trypanosoma brucei group are found in sub-Saharan Africa. Although the past two decades has witnessed commendable research efforts and technical advances in our understanding of the biochemistry, molecular and cell biology of these pathogens, the dreaded protozoal diseases caused by these organisms threaten mankind. Therapeutic tools for the treatment of most parasitic diseases are extremely limited. The development of parasites resistant to many of the available drugs is also responsible for the depressing picture of disease persistence and death. Development of commercially available vaccines is still far from reality, though research and trial programs continue.